2010
DOI: 10.1177/0887403410375109
|View full text |Cite
|
Sign up to set email alerts
|

Halfway Back: An Alternative to Revocation for Technical Parole Violators

Abstract: Over the past three decades, concomitant increases in prison population and the use of parole, coupled with a more punitive parole philosophy and fiscal crises at every level of government, have prompted a renewed interest in intermediate sanctions— especially for technical parole violators. A number of jurisdictions have developed intermediate sanctions that are both custodial and therapeutic—but do not involve a return to prison—for technical violators. Despite their growing popularity, little research has e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…DRC participants experienced similar results as the HWB group. White et al (2011) found similar results when evaluating the HWB program from a cost perspective. The costs associated with recidivism and incarceration were significantly less for offenders in the HWB program compared to control subjects.…”
Section: Halfway Towards Reentrysupporting
confidence: 84%
See 2 more Smart Citations
“…DRC participants experienced similar results as the HWB group. White et al (2011) found similar results when evaluating the HWB program from a cost perspective. The costs associated with recidivism and incarceration were significantly less for offenders in the HWB program compared to control subjects.…”
Section: Halfway Towards Reentrysupporting
confidence: 84%
“…Overall, HWHs have been effective in reentry practice (Austin, 2001;MacKenzie, 2000;Seiter & Kadela, 2003;Marion, 2002;Zhang, Roberts, & Callanan, 2006a, 2006b. HWH programs that adhere to the tenets of the RNR model have been especially effective (Clear & Schrantz, 2011;Bouffard, MacKenzie, & Hickman, 2000;Lowenkamp & Latessa, 2005;Lowenkamp, Latessa, & Smith, 2006;Ostermann, 2009;Taxman, Rexroat, Shilton, Mericle, & Lerch, 2010;White, Mellow, Englander, & Ruffinengo, 2011). It is common that interventions may be tailored (i.e., offenders with substance abuse issues may be placed in facilities that primarily offer drug treatment counseling while offenders with employment issues may be placed in facilities that offer offender employment assistance, vocational training, and work release programs).…”
Section: Halfway Towards Reentrymentioning
confidence: 96%
See 1 more Smart Citation
“…Although there have been almost no studies of back-end net-widening in the parole population (White et al 2011), the same theoretical argument applies: the use of custodial sanctions for parole violations—especially for minor technical violations—could widen the net of penal control by increasing the probability of imprisonment for subsequent violations and expanding the population ensnared in this net to include parolees at low risk of recidivating. Moreover, facilities and programs intended to divert technical violators from prison may expand once created, and the availability of such facilities and programs can then create additional demand for them, sweeping into the widening net individuals who would have previously received non-custodial sanctions.…”
Section: The Expansion Of Community Supervision Net-widening and Cumentioning
confidence: 99%
“…In the United States alone, this measure is very heterogeneous (Kilburn and Costanza, 2011). It is aimed simultaneously at former prisoners released on parole (Latessa and Allen, 1982), at convicts whose parole has gone wrong (White et al, 2011), and at other types of profiles such as convicts with psychiatric disorders (Gumrukcu, 1968;Carpenter, 1978). Moreover, existing papers use different outcomes to estimate the effect of semi-liberty: the probability of failing the measure and therefore of being re-incarcerated (Walsh and Beck, 1990), the probability of being sentenced again following a new offense (Constanza et al, 2015), or the crime rate at the local level following the opening of a new semi-liberty facility (Hyatt and Han, 2018).…”
Section: Introductionmentioning
confidence: 99%